Faiths and children from Islamic perspective - Mohd, Azizah (2015)
Islam is a divine religion revealed through the messenger of God (Allah the almighty), the teaching of which is manifested through the Quran and the Sunnah of the Prophet (saw). Islam rules that all conformity with the Quranic Provisions and Prophets teaching is rewarded and non conformity without excuse is punished in the hereafter. Therefore faith in Islam is only complete when one has faith in Allah as the god, Prophet as messenger, Quran (the book from God that contains the teaching of Islam),the day of judgement. In addition, Muslims are to strongly believe that anything happened in their life is destined by Allah and that they must always redha with their fate. Islam regards children as a bounty and trust from Allah the God. Children are bounties from Allah (s.w.t.). They are the most valuable property gifted by Allah (s.w.t.) to decorate the parent’s life and their family. This paper seeks to examine Islamic faith and Chilren Rights from Islamic Perspective.